2009
DOI: 10.1007/s10658-009-9533-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pathogenicity and aggressiveness of F. langsethiae on oat and wheat seedlings relative to known seedling blight pathogens

Abstract: Fusarium and Microdochium species are causal agents of seedling blight of small-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…In fact, this fungus is known for its inability to cause severe disease symptoms on cereals (e.g. : wheat and oat) without apparent loss of grain yield (Torp and Adler 2004;Imathiu et al 2010;Divon et al 2011). Nowadays the relation between grain characteristics and the presence of DON and T2+HT2 are not sufficient to draw comprehensive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this fungus is known for its inability to cause severe disease symptoms on cereals (e.g. : wheat and oat) without apparent loss of grain yield (Torp and Adler 2004;Imathiu et al 2010;Divon et al 2011). Nowadays the relation between grain characteristics and the presence of DON and T2+HT2 are not sufficient to draw comprehensive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The present study goes one step further by examining the impact of aphids on fungal biomass accumulation in seedlings as well as ear infection. It was not previously known if F. langsethiae was capable of colonizing wheat seedlings systemically as a result of seed infection; infection attempts have only been measured visually, and no symptoms were seen (29). This study showed that seedling colonization measured by pathogen DNA can be achieved using spray inoculation with a high concentration of inoculum (10 7 spores ml Ϫ1 ) and that pretreatment of seedlings with aphids increases fungal biomass accumulation 4-fold in seedlings following inoculation.…”
Section: Discussionmentioning
confidence: 78%
“…Fusarium langsethiae isolates produced necroses of different sizes on wounded detached oat and wheat leaves, but not on unwounded wheat leaves (Imathiu et al 2009). Furthermore, F. langsethiae did not cause seedling blight after artificial inoculation of oat and wheat seeds (Imathiu et al 2010). On artificially inoculated oats, panicle infection was shown to be the prime route of infection for F. langsethiae, with symptoms evident after both injection and spray inoculation at different concentrations (Divon et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, F. langsethiae did not cause seedling blight after artificial inoculation of oat and wheat seeds (Imathiu et al. ). On artificially inoculated oats, panicle infection was shown to be the prime route of infection for F. langsethiae , with symptoms evident after both injection and spray inoculation at different concentrations (Divon et al.…”
Section: Discussionmentioning
confidence: 99%